Transcending hunter gatherer pursuits while balancing customary cultural ideals with market forces of advanced western societies: Extending the traditional boundaries of indigenous Yolngu people of the Northern Territory of Australia - Pearson, Cecil; Daff, Sandra (Sage Publications, 2013)
As large multinationals move their operations into remote regions of the world, imperatives of social responsibility and sound business pragmatism compel engagement of the marginalized local Indigenous people. This notion is particularly relevant for the mining industry in Australia, which is undertaken in remote regions, where the local Indigenous communities are significantly socio-economically disadvantaged compared to other Australians. This article reports the job-related outcomes of Indigenous Yolngu people of East Arnhem Land in the Northern Territory of Australia who were participants in a unique vocational-educational programme set up by the multinational mining company Rio Tinto Alcan. These mainline job-related outcomes are in two main areas: (1) employment in mainline work at the Nhulunbuy refinery or the mine site and (2) entrepreneurial timber-related business (milling timber, house construction, furniture manufacture). Both streams are inaugural achievements for these Indigenous Australians. The concluding sections present challenges for multinational corporations when anchoring institutional processes, structures and the contemporary technologies of the workplace with the contextuality of rural Australian communities.